THE ANALYSIS OF EFL COLLEGE STUDENTS PERSPECTIVE ON ONLINE LANGUAGE LEARNING DURING COVID-19 PANDEMIC - Sri Wahyuni Hasibuan (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The purpose of this study is to find out students’ perspective on online language learning during the COVID-19 pandemic and to provide the reasons why their perspective in the way they. The study uses qualitative descriptive research. The subject of this research was 25 English Education Department students of STAIN Mandailing Natal. The data is taken from questionnaire that consists of 15 questions with 4-level Likert Scale, labelled by strongly disagree, disagree, agree, and strongly agree to find out students perspective on online language learning and from interview sheets.. The result of this research is EFL College students have negative perspective on online language learning during Covid-19 pandemic. The reasons why they have negative perspective were they have so many obstacle during online class, the understanding of material is also weak, the English improvement isn’t significantly increase and they are don’t agree that online class should be continued to be carried out.